Strengthening the Innovation Process and Competitive Advantage of Mie Sidoarjo MSMEs to Penetrate the Export Market in Achieving the SDGs - Sutomo, Sutomo; Sudarmiatin, Sudarmiatin; Handayati , Puji (Publisher Cv. Inara, 2025)
In the era of globalization, MSMEs in the processed food sector have a great opportunity to penetrate the export market through the use of innovation and competitive advantage. One concrete example is CV. Indigo Sejahtera in Sidoarjo, a producer of processed egg noodles that has successfully entered international markets such as Malaysia, Singapore, and Saudi Arabia. This phenomenon shows the great potential of local MSMEs to compete in the global market. However, there is still a research gap related to operational strategies that MSMEs actually apply in achieving sustainable export competitiveness. The novelty of this research is in the form of an in-depth exploration of the integration of innovation processes and competitive advantages in supporting the success of MSME exports based on processed foods. The urgency is based on the strategic role of MSMEs in encouraging inclusive economic growth and industrial sustainability in accordance with the SDGs agenda. Qualitative research method phenomenological approach, this research was carried out in CV. Indigo Sejahtera, with one main informant of the owner and two informants supporting employees. The results of the study show that the strategies implemented include product innovation through a variety of flavors ranging from spicy, original, spices, attractive and socially proofable packaging innovations for social media, as well as active digital marketing through live TikTok, Shopee, and Instagram twice a day in the afternoon and evening, as well as the management of the official website. Competitive advantages are obtained from affordable prices, distinctive tastes, and unique packaging, as well as collaborations with local food influencers as endorsements. This strategy has proven effective in increasing global competitiveness. The implications of this study lead to the real contribution of MSMEs to the achievement of the SDGs, especially the goals of 8 decent work and economic growth and the goals of 9 industry, innovation, and infrastructure.